Individuals in sober living: Effects of contact with substance using family members. Issue 2 (3rd April 2022) - Soto-Nevarez, Arturo; Reilly, Angela; Stevens, Ed; Bobak, Ted J.; Jason, Leonard A.
Abstract: This study examines the effects that substance-using family members have on those working to maintain recovery from substance use disorder. Participants ( N  = 229) were recruited from Oxford Houses (OH) across North Carolina, Texas, and Oregon. A stepwise linear regression with variables including abstinence self-efficacy, gender, substance use, attendance of Alcoholics Anonymous, and conflict with family and non-family was run to examine associations between the amount of substance using family members in the participant's social network. The abstinence self-efficacy mean score, gender, and days of serious conflict with non-family members were significantly associated with total number of substance-using family members in a participant's social network. These results may indicate that OH's serve as a buffer between substance using family members and one's abstinence self-efficacy. It remains unclear if individuals are at an increased risk of relapse from this familial influence when perceived abstinence self-efficacy drops. If so, OH residents could benefit from interventions that help them maintain their perceived abstinence self-efficacy.